Decision-making model for production and operation of underground gold mines considering low-carbon condition - Jie Hou; Yingyu Gu; Guoqing Li; Guangjun Guo; Qianqian Yu (Scientific Reports)
Abstract Within the framework of a low-carbon transition and integrated mineral resource exploitation, this study presents an innovative system dynamics (SD) model designed to optimize decision-making and enhance profitability in underground gold mining operations. The novel approach seamlessly integrates critical subsystems, including reserves, mining, ore dressing, smelting, financial, and carbon reduction, offering a comprehensive framework for the analysis of efficiency and sustainability. Utilizing causal loop and system flow diagrams, the model elucidates the synergistic impacts of index variations on mine operational efficiency. The model is applied to a case study involving three mining areas within a specific gold mine in China, where sensitivity analysis identifies key indicators affecting profitability. Furthermore, it examines dynamic trends under varying carbon tax scenarios. The findings reveal that mining strategic adjustments can significantly enhance profitability, extend the operational lifespan of mines, and reduce emissions.